(untitled) (International Journal of Nursing Ethics, and Health Care Management, 2026)
Christianity spread in Tanzania as the work of groups of different missionaries tied to various denominations which represented the division of European societies and churches. For the first time, Christianity entered Mbeya Region in the 1890s through the Moravian Missionaries and later followed by missionaries from other denominations including: Catholic, Anglican, Lutheran, Pentecostal and the like. Specifically, and for the purpose of narrowing the scope, this study addressed the three groups of missionaries namely; Moravian Missionaries, Lutheran Missionaries and the Catholic Missionaries (White Fathers) from 1891 to 1980. Along with the spread of Christianity, among many activities done by these missionaries was the provision of health services. This study therefore, investigated a historical analysis of the impact of missionary healthy activities on local communities of Mbeya from 1891 to 1980. Using Qualitative Approach, in-depth interview was conducted with 7 community members and 5 local health providers. Concurrently, this approach enhanced collection and interpretation of research data from secondary sources and Tanzania National Archive. The study intended to come up with findings about the situation of the African health services before the coming of European missionaries and how was it affected by the introduction of the European Medical services. In this regard, it was found that although the people of Mbeya had benefited from the services given to them by the missionaries, their traditional ways of life had totally been transformed into Western System of Life. This included for example, traditional medicine which is not now really in practice and instead, people have been shifted to the wing of Western Medicines. The study further concluded that missionary health activities had to some extent facilitated the coming and flourishment of European imperialists on the land of people of Mbeya something that had created unforgettable repercussions on the respective people.